Anwar Ibrahim : semangat darah muda - Zairudin Hashim; Angkatan Belia Islam Malaysia (Kuala Lumpur, Malaysia : Angkatan Belia Islam Malaysia, 2019)
On leadership and political role of Anwar Ibrahim, a politician in Malaysia.
Includes bibliographical references (page 135).
In Malay.
Keywords: Anwar Ibrahim, -- 1947-; Politicians -- Malaysia; Leadership -- Malaysia; Malaysia -- Politics and government -- 21st century